INTERVENSI AKUPUNTUR TERHADAP KEKUATAN OTOT PADA PASIEN STROKE: STUDI LITERATUR REVIEW - Ulkhasanah, Muzaroah Ermawati; Widiastuti, Agung; Sani, Fakhrudin Nasrul (Coping: Community of Publishing in Nursing; Vol 9 No 6 (2021): Desember 2021, 2021)
Background: Stroke occurs when a blood vessel bursts which results in part of the brain not getting a blood supply that carries oxygen, resulting in cell and tissue death. Non-pharmacological modification therapy can be given with those that can improve the nervous system, improve body condition and increase muscle strength. Purpose: from this study to determine the effect of acupuncture intervention on increasing muscle strength in stroke patients by looking at several studies conducted Research Methods: with a literature study, the author conducted a literature study by conducting an internet-based search through PubMed, google bachelor and ProQuest on various written sources , both journals and articles that are relevant to the problems studied from 2012 to 2020. Results: what has been obtained from the provision of acupuncture therapy to increase muscle in stroke patients, as many as 7 journals have studied that acupuncture therapy is either single therapy or combination therapy can have an effect on increasing muscle strength. Conclusion: acupuncture has an effect on increasing muscle strength in stroke patients.